Practice and prestige : an exploration of Neolithic warfare, Bell Beaker archery, and social stratification from an anthropological perspective - Ryan-Despraz, Jessica, (Archaeopress Archaeology, 2022)
Drawing on the author's recent study that assessed the bone morphology of skeletons in Bell Beaker burials for signs of specialised archery activity, this book contextualises the osteological findings and explores the evidence for warfare and archery throughout the Neolithic period in general and the Bell Beaker period in particular.